Study of lanthanum aluminate for cost effective electrolyte material for SOFC - Verma O.N.; Shahi A.K.; Singh P. (My University, 2025)
The perovskite type electrolyte material LaAlO3 (abbreviated LAO) has been prepared by easy processing of auto-combustion synthesis using lanthanum nitrate and aluminium nitrate salts as precursors and citric acid as the fuel. The XRD analysis reveals that as synthesized material exhibits only single phase having rhombohedral structure. The measured density and theoretical density have been deliberated. The temperature dependent electrical conductivity of LAO increases with increasing the temperature which leads to increased mobility of oxide ion. The major contribution of such a significant value of ionic conductivity of LAO can be inferred to grain boundary resistance. © 2018 Author(s).